ENGLISH–QUR’ANIC IMPACT ON HADITH IN IDEAS AND STYLE - Muhammad Iqbal; Arsha Munir Leghari (دی اسکالر)
This research paper discusses the significance of the literary level of Qur’an and its direct impact on the sayings of Prophet Muhammad (SAW). Qur’an is the word of God which is unchangeable and unquestionable and contains fundamentals and rules, regarding different aspects of life, whether religious, social, political, economic or legal matters and Ahadiths are important because the Prophet (PBUH) was the final and perfect messenger to follow and Ahadiths expand on the Qur’an and they are interlinked so are the two main (primary) sources which they never disagree, but rather complement each other. Moreover the Qur’an gives a brief teaching the Ahadiths are referred to for fuller details, similarly where the Qur’an is silent on a point the Ahadiths are referred to, so both they are the authority for the foundation of legal matters. The Qur’an is an authority in Islamic law; it is the word of God; it is not questioned or contradicted by the other sources; the Sunnah is the Prophet’s example and is recorded in the hadith. Literally Qur’an and Sayings of Prophet are both in Arabic language but they are two different styles.